Reinterpretation of “Fitna” in QS. Al-Baqarah Verse 191 (Ma'na Cum Maghza Approach) - Hakam al-Ma'mun; Haris Fatwa Dinal Maula (Aqwal: Journal of Qur'an and Hadis Studies, 2021)
The meaning of the word â€œfitnaâ€ in Indonesian is often incorrect when it is associated with the word of Allah written in QS. al-Baqarah: 191. The snippet of the verse is al-fitna asyaddu min al-qatl, which if translated reads more or less "slander is more cruel than murder". Misunderstanding can occur when the translation of a verse occurs partially and independently from the context of the verse in which it was derived. Apart from the partial translation problem, another factor is the distortion of the meaning of the word slander (fitna) in Indonesian and Arabic. Through the ma'na cum maghzÄ approach, the misunderstanding of the word fitna is then traced so that some basic meanings are known, namely al-ibtilÄ, al-ikhtibÄr, al-imtihÄn and al-ihrÄq. The word slander in the context of QS. al-Baqarah: 191 is closer to the meaning of al-syirk (shirk) than to the meaning of fitna (slander) as understood in the Indonesian language, which is to convey false information to others. The reading of the verse through the ma'na cum maghzÄ approach then raises several main messages from this verse, namely the message of monotheism, maqÄá¹£id al-syarÄ«'ah and social ethics. These values synergize with each other to support preventive action against the fitna referred to by the verse.